The Effect of Learning Interest on Student Learning Outcomes in Islamic Religious Education Subjects for Junior High School Students - Anwar Maulana (Sufiya Journal of Islamic Studies, 2024)
This study aims to determine the effect of interest in learning on student learning outcomes in Islamic Religious Education (PAI) subjects in class VIII of SMP Negeri 29 Medan City. This type of research is quantitative research with a correlational approach. The sample in this study amounted to 50 student respondents selected by total sampling. Data collection techniques using questionnaires and documentation of student learning outcomes. The results showed that the correlation coefficient (r) value was 0.42, which based on the interpretation table was included in the category of a fairly strong relationship. Furthermore, the calculation of the coefficient of determination shows that interest in learning contributes 17.64% to learning outcomes, while the remaining 82.36% is influenced by other factors. Hypothesis testing shows that the t_count value of 3.204 is greater than the t_table of 2.010, so Hₐ is accepted and H₀ is rejected. Thus, there is a significant influence between interest in learning on student learning outcomes in Islamic Religious Education subjects at SMP Negeri 29 Medan City.